ANALISIS PAJAK PERDAGANGAN INTERNASIONAL, TINGKAT SUKU BUNGA, JUMLAH UANG BEREDAR TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Rizky, Reni; Fuddin, Muhammad Khoirul (Program Studi Ekonomi Pembangunan, 2024)
Economic is an important indicator for the progress of a country. In the midst of global economic dynamics, countries around the world are trying to optimize factors that can influence their economic growth. The aim of this study is to analyze the influence of international trade taxes, interest rates and money supply on economic growth in Indonesia. The research method used is multiple linear regressions for the period 1991–2021. The research results show that the trade tax variable has a positive and not significant effect on economic growth. The interest rate variable has a significant positive effect on economic growth. Meanwhile, the money supply variable has a significant negative effect on economic growth in Indonesia.